2017
DOI: 10.18632/oncotarget.20938
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of S-1 with concurrent radiotherapy in elderly patients with esophageal cancer

Abstract: BackgroundConcurrent chemoradiotherapy (CCRT) using conventional platinum-based doublets are often associated with significant incidence of toxic effects in elderly patients with esophageal cancer. We previously reported a phase I trial of CCRT using S-1, an oral 5-fluorouracil derivative, which yielded well safe and active outcomes.MethodsPatients with histologically confirmed esophageal cancer, who were age of 70 years or older with performance status (PS) score of 0-2 or age of 66 to 69 with PS score of 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In our systematic review, we found that the two prospective trials by Servagi-Vernat et al 8 had criteria excluding patients with weight loss of more than 15% from baseline. In another Phase II trial conducted by Ji et al, 10 weight loss was not used as an exclusion criterion, but over half of the patients (17/30, 56.7%) had <10% weight loss over nearly 6 months. Fourteen of the 24 retrospective studies did not reveal any results related to nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…In our systematic review, we found that the two prospective trials by Servagi-Vernat et al 8 had criteria excluding patients with weight loss of more than 15% from baseline. In another Phase II trial conducted by Ji et al, 10 weight loss was not used as an exclusion criterion, but over half of the patients (17/30, 56.7%) had <10% weight loss over nearly 6 months. Fourteen of the 24 retrospective studies did not reveal any results related to nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the survival benefit of CCRT in elderly patients, a single-centre retrospective analysis (12) has previously shown that age 70 years or older is a poor prognostic factor (HR =2.099, P=0.001) for CCRT, however, all patients in the CCRT group were treated with the cisplatin plus 5-florouracil (FP) or paclitaxel plus cisplatin (TP) regimen in this study, and the results might indicate that two-drug intravenous chemotherapy in combination with concurrent radiotherapy does not provide survival benefit in elderly patients. In contrast, single-drug regimens, especially S-1 as a single oral agent, in combination with concurrent radiotherapy for elderly patients with esophageal cancer has received much focus in recent years (13)(14)(15). Therefore, for elderly patients aged 70 years or older, the potential survival benefit of CCRT, as well as optimal treatment regimens require further research (English Language Editor: J. Teoh)…”
Section: Discussionmentioning
confidence: 99%
“…[25] In a prospective study of 30 patients received CCRT with S-1 (70 mg/m 2 ), the 2-years PFS and OS was 40.8% and 45.1%, respectively. [26] However, no study has directly compared the e cacy and safety of concurrent DP and S-1 regimens combined with RT in ESCC. In this study, the 3-year OS and 3-year PFS in the S-1 group was 34.7% and 25.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%